Could diffuse coevolution explain the generic eggshell color of the brown-headed cowbird?. Issue 6 (23rd September 2021) - Hanley, Daniel; Moghaddame-Jafari, Beheshteh; Rutledge, Samantha L
Abstract: The brown-headed cowbird (hereafter cowbird) is an avian brood parasite that produces an egg dissimilar to those produced by the majority of its diverse host community. The cowbird's generic egg may result from a Jack-of-all-trades strategy; however, the evolutionary mechanisms that select for their generic eggs are unclear. Here we propose that the cowbird's eggshell phenotypes have evolved via diffuse coevolution, which results from community-level selective pressures, rather than via pairwise coevolution that occurs between a particular host species and its brood parasite. Under diffuse coevolution the cowbird's host community, with varying eggshell phenotypes and recognition abilities, would select for a cowbird eggshell phenotype intermediate to those of its host community. This selection is exerted by hosts that reject cowbird eggs, rather than those that accept them; therefore, we expect cowbird eggshell colors can be approximated by both the phenotypes and rejection abilities of their host community. Here we use eggshell reflectance data from 43 host species to demonstrate that the cowbird eggshell phenotypes are reasonably predicted (within 2 just noticeable differences) by the eggshell phenotypes and rejection rates of their hosts. These findings suggest that cowbird eggshell phenotypes, and potentially those of other some generalist parasites, may evolve via diffuse coevolution. Importantly, this research provides insight into the underlying evolutionary processes that explain observed phenotypic variation and provides a framework for studying selection on both specialist and generalist parasites' traits.